1967
DOI: 10.3109/00365526709180063
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Abnormal Bacterial Proliferation in the Gastrointestinal Tract after Gastric Surgery

Abstract: DELLIPIANI, A. W. & GIRDWOOD, R. H. The Significance of Abnormal Bacterial Proliferation in the Gastrointestinal Tract after Gastric Surgery. Scand. J. Gastroent. 2, [161][162][163][164][165][166][167][168]1967. The juices of the stomach or stomach remnant and of the jejunum of twenty-one patients who had undergone gastroenterostomy and twenty-six patients with partial gastrectomy have been studied for the presence of faecal type organisms as represented by Enterobacteriaceae, Streptococcus faecalis and Clostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1969
1969
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…It might be expected that patients with postvagotomy diarrhoea would have a higher incidence of colonization with faecal type organisms, but the incidence of colonization in such patients was no higher than in controls and, although 'anaerobic colonization' was more common, statistical significance was not reached. This confirms previous reports on small numbers of patients (Dellipiani and Girdwood, 1967;Tinker, Hoffbrand, Mitchison, Tabaqchali, and Cox, 1971). In the first two postoperative weeks, Clostridium welchii has been particularly implicated (Howie, Duncan, and Mackie, 1953), but a more recent quantitative study has not confirmed this (Browning et al, 1969), and in the present study, on average four years following surgery no single pathogenic organism could be isolated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It might be expected that patients with postvagotomy diarrhoea would have a higher incidence of colonization with faecal type organisms, but the incidence of colonization in such patients was no higher than in controls and, although 'anaerobic colonization' was more common, statistical significance was not reached. This confirms previous reports on small numbers of patients (Dellipiani and Girdwood, 1967;Tinker, Hoffbrand, Mitchison, Tabaqchali, and Cox, 1971). In the first two postoperative weeks, Clostridium welchii has been particularly implicated (Howie, Duncan, and Mackie, 1953), but a more recent quantitative study has not confirmed this (Browning et al, 1969), and in the present study, on average four years following surgery no single pathogenic organism could be isolated.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequent quantitative studies following gastrectomy have not confirmed this finding (Wirts and Goldstein, 1964;Tabaqchali and Booth, 1966;Dellipiani and Girdwood, 1967;Gorbach and Tabaqchali, 1969) nor was it confirmed after vagotomy and gastroenterostomy (Dellipiani and Girdwood, 1967). The present study has sought, for the first time, to correlate the faecal fat excretion and the small intestinal flora in patients with diarrhoea following gastric surgery.…”
Section: Discussionmentioning
confidence: 78%
“…Bac terial invasion of the small intestine resulting from achlorhydria and stasis in the afferent loop accounts sometimes for steatorrhoea [4,8,17], This pos sibility was excluded in our patient since the jejunal content did not show an increased amount of bacteria. Protein-loosing enteropathy and primary mal absorption due to an atrophy of the intestinal villi, which are sometimes responsible for malnutrition in a gastrcctomized patient, were also excluded [3,11].…”
Section: Discussionmentioning
confidence: 99%
“…Steatorrhoea is a well recognized complication of gastroenterostomy and vagotomy though our own incidence of this is slightly lower than that of Cox and his colleagues (1964). The causes of steatorrhoea in these patients are likely to be multiple and have been discussed elsewhere (Dellipiani and Girdwood, 1967). ALTERNATIVE PROCEDURES In the light of these results it is worth considering alternative surgical procedures for the management of chronic duodenal ulcer.…”
Section: Metabolic Studiesmentioning
confidence: 99%